Advanced atomic force microscopies and their applications in two-dimensional materials: a review. (1st September 2022) - Xu, Rui; Guo, Jianfeng; Mi, Shuo; Wen, Huanfei; Pang, Fei; Ji, Wei; Cheng, Zhihai
Abstract: Scanning probe microscopy (SPM) allows the spatial imaging, measurement, and manipulation of nano and atomic scale surfaces in real space. In the last two decades, numerous advanced and functional SPM methods, particularly atomic force microscopy (AFM), have been developed and applied in various research fields, from mapping sample morphology to measuring physical properties. Herein, we review the recent progress in functional AFM methods and their applications in studies of two-dimensional (2D) materials, particularly their interfacial physical properties on the substrates. This review can inspire more exciting application works using advanced AFM modes in the 2D and functional materials fields.